Dinamika Pola Kepemimpinan Adat di Dusun Adat Karampuang Sulawesi Selatan - Fakhira Yaumil Utami; Ni Luh Arjani; Ni Made Wiasti Ni Made Wiasti (Sunari Penjor : Jurnal of Anthropology, 2020)
This research discusses the dynamics of customary leadership patterns in the Karampuang customary hamlet of South Sulawesi and the impact of these dynamics. The problems that will be discussed in this research are (1) Why is there a dynamic of customary leadership patterns in Karampuang village (2) What is the impact of the dynamics of customary leadership patterns in Karampuang customary village. This research is a qualitative research using social change theory and leadership theory. as a basis for answering both problems. The results of this study reveal that the dynamics of customary leadership patterns in the Karampuang customary village are influenced by internal factors and external factors. The dynamics of customary leadership towards the community can be classified into several fields, namely the impact in the legal and environmental, economic, socio-cultural fields all of which have a beneficial impact on indigenous peoples; whereas the field of education is less profitable for indigenous peoples due to less motivation to demand higher education.